2023
DOI: 10.3390/cells12040671
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Drug Repurposing: Focus on Vasodilators

Abstract: Drug repurposing aims to identify new therapeutic uses for drugs that have already been approved for other conditions. This approach can save time and resources compared to traditional drug development, as the safety and efficacy of the repurposed drug have already been established. In the context of cancer, drug repurposing can lead to the discovery of new treatments that can target specific cancer cell lines and improve patient outcomes. Vasodilators are a class of drugs that have been shown to have the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 199 publications
0
5
0
Order By: Relevance
“…One example is nitroglycerin, which has shown promising results in lung cancer patients when used in combination with cisplatin, leading to improved response rates and longer time to progression [ 167 ]. Similarly, a clinical trial using slow-releasing nitroglycerine patches in men with high levels of prostate-specific antigen (PSA) after primary therapy resulted in a prolonged PSA doubling time, suggesting that nitric-oxide-induced inhibition of hypoxia-mediated progression may play a role in the observed therapeutic effects (NCT01704274) [ 168 ]. As a nitric oxide donor, nitroglycerin could inhibit NF-κB through S-nitrosylation, which could consequently interfere with NF-κB binding to DNA [ 169 , 170 ].…”
Section: The Roles Of Yy1 In Tumor Development and Progressionmentioning
confidence: 99%
“…One example is nitroglycerin, which has shown promising results in lung cancer patients when used in combination with cisplatin, leading to improved response rates and longer time to progression [ 167 ]. Similarly, a clinical trial using slow-releasing nitroglycerine patches in men with high levels of prostate-specific antigen (PSA) after primary therapy resulted in a prolonged PSA doubling time, suggesting that nitric-oxide-induced inhibition of hypoxia-mediated progression may play a role in the observed therapeutic effects (NCT01704274) [ 168 ]. As a nitric oxide donor, nitroglycerin could inhibit NF-κB through S-nitrosylation, which could consequently interfere with NF-κB binding to DNA [ 169 , 170 ].…”
Section: The Roles Of Yy1 In Tumor Development and Progressionmentioning
confidence: 99%
“…Previously, we evaluated the combination of levosimendan with 5-fluorouracil (5-FU), an antineoplastic drug, and found that this drug could help increase the cytotoxicity of 5-FU, decreasing the viability of bladder cancer cells [ 20 ].…”
Section: Repurposing Levosimendan For Oncologymentioning
confidence: 99%
“…This combination demonstrated a significantly greater reduction in cell viability compared to using the repurposed drug individually. Particularly noteworthy was the combination of 100 μM of levosimendan with the IC50 value of 5-FU (13.41 μM), which resulted in an impressive 59% decrease in cell viability compared to treating with 100 μM of levosimendan alone [ 20 ].…”
Section: Repurposing Levosimendan For Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of vasodilators include drugs such as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, calcium channel blockers, nitrates, PDE5 inhibitors, and endothelin antagonists, among others. These drugs work through different mechanisms to relax the smooth muscles in blood vessels, thereby reducing blood pressure and improving blood flow throughout the body [ 7 ].…”
Section: Introductionmentioning
confidence: 99%